The Calliphoridae (Diptera) of Armenia - Rognes, Knut (Zootaxa, 2019)
A report is given on the Calliphoridae (Diptera) collected by Adrian C. Pont during recent fieldwork in Armenia. Twenty-six (26) named species have been identified, and of these 21 are newly recorded from Armenia. Various taxonomic characters of Pollenia paragrunini Rognes, 1988, including the large variation in the width of the male frons, are discussed. One new species is described: Pollenia agneteae sp. nov., and is assigned to the Pollenia semicinerea species-group.